Printed-circuit antennae on non-reciprocal magnetic thin films - Yang, Hung-Yu; Alexopoulos, Nicolaos G. (Thin solid films, 1992)
The applications of printed-circuit antennae on non-reciprocal magnetic thin films are discussed. Accurate circuit models based on a full-wave numerical analysis are described. These models are essential to the design of microwave- and millimeter-wave integrated circuits with ferrites. The advantages of using ferrite substrates in printed-circuit antennae including pattern shaping, scattering control and high gain, are highlighted. Future research on related subjects is also discussed.